Peningkatan Keterampilan Menulis Karangan Deskripsi melalui Model Pembelajaran Menulis Think-Talk-Write (TTW) dengan Media Visual pada Siswa Kelas IV SDN Inpres 3 Talise - Asmarine, Asmarine (Bahasantodea, 2016)
The purpose of this research is to decsribe the improving student activity i writing learning of descriptive essay with the think talk write model through visual media and to decsribe improving writing skill in descriptive essay in this content of aspect, using of spelling, diction and also using of read symbols with think talk write model with the visual media. The kind of this research is class action research which implemented of the fifth grade student of SDN Inpres 3 Talise. This research is following the model is developed by kemmis through class action research planning which implemented with cycle. They are planning, implementing, observation, and reflection. Based on this result of writing skill in descriptive essay through think talk write model with the visual media of the fifth grade student at SDN Inpres 3 Talise can improve student activity. The result of observation at the indonesian learning is in the writing skill in descriptive essay at the cycle (I) the data studet activity get average score 2,15 with the category is enough. At the cycle (II) the data student activity with the average score is 2,76 with the category is good. Writing skill in descriptive essay through think talk write learning of writing model with the visual media of the fourth grade student at SD Inpres 3 Talise can improve student writing skill. It is can be seen from the observation result of indonesian learning that is student writing skill with the data cycle (I) the average score is 2,23 with the category is enough. At the cycle (II) the average score is 3,08 with the category is good. Student writing skill has achieved succesfull of indicator lacks is good. With this improving of student writing skill had achieving succesfull indicator. So, the result of indonesian learning specifically in writing descriptive essay is improve.